The development of a novel model of directfracture healing in the rat. Issue 11 (November 2012) - Savaridas, T.; Wallace, R. J.; Muir, A. Y.; Salter, D. M.; Simpson, A. H. R. W.
Abstract : Objectives: Small animal models of fracture repair primarily investigate indirect fracture healing via external callus formation. We present the first described rat model of direct fracture healing. Methods: A rat tibial osteotomy was created and fixed with compression plating similar to that used in patients. The procedure was evaluated in 15 cadaver rats and then in vivo in ten Sprague-Dawley rats. Controls had osteotomies stabilised with a uniaxial external fixator that used the same surgical approach and relied on the same number and diameter of screw holes in bone. Results: Fracture healing occurred without evidence of external callus on plain radiographs. At six weeks after fracture fixation, the mean stress at failure in a four-point bending test was 24.65 N/mm 2 (sd 6.15). Histology revealed 'cutting-cones' traversing the fracture site. In controls where a uniaxial external fixator was used, bone healing occurred via external callus formation. Conclusions: A simple, reproducible model of direct fracture healing in rat tibia that mimics clinical practice has been developed for use in future studies of direct fracture healing.